Sociology on the Move in the Researchscapes. Theory and Empirics in XVII ISA World Congress of Sociology - Žilinskaitė, Viktorija (Sociologija. Mintis ir veiksmas, 2010)
Attempts to analyse entire Congress of Sociology, whether European, whether World can only sound naïve. The article focuses on relations between sociological theory, social critics and empirical research. The XVII ISA World Congress of Sociology is used as reflection contemporary sociological field. The article concentrates on few of trends in sociology that may lead to enlargement of focus of sociological research or re-establishing of borders of sociology. It depends on success of the researches and strength of emerging theories. Strength in explanatory terms is not enough for today’s sociology. Sociology rather needs the strength to break institutional pressures tying sociology to power-serving routines and everyday common practices demanding applicable product. The article by no way argues that applicability or routines are vain or valueless. It, on contrary, notices that lots of established theories emerged form abundance of empirical observations and applied researches, giving insights for frontier researches, although not all empirical surveys lead to theory creation.
Keywords: sociology of science; researchscape; sociological theory; empirical research